Ecospirit : religions and philosophies for the earth - Kearns, Laurel; Keller, Catherine, 1953- (Transdisciplinary theological colloquia., 2007)
"We hope--even as we doubt--that the environmental crisis can be controlled. Public awareness of our species' self-destructiveness as material beings in a material world is growing--but so is the destructiveness. The practical interventions needed for saving and restoring the earth will require a collective shift of such magnitude as to take on a spiritual and religious intensity. This transformation has in part already begun. Traditions of ecological theology and ecologically aware religious practice have been preparing the way for decades. Yet these traditions still remain marginal to society, academy, and church. This book probes the possibility of a green shift radical enough to permeate the ancient roots of our sensibility and the social sources of our practice. From new language for imagining the earth as a living ground to current constructions of nature in theology, science, and philosophy; from environmentalism's questioning of postmodern thought to a garden of green doctrines, rituals, and liturgies for contemporary religion, these chapters explore and expand our sense of how to proceed in the face of an ecological crisis that demands new thinking and acting."--Publisher's abstract